Kelayakan Media Booklet pada Submateri Keanekaragaman Hayati Kelas X - Untung; Syamswisna; Titin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to determine the feasibility of booklet media for class X high school biodiversity material. The method used in this research is research and development. The procedure used is the development model according to Borg & Gall which is adapted to the needs of researchers. The Borg & Gall development procedures are potential and problems, data collection, product design and design validation. The validation instrument used in this research was the booklet media validation sheet. Validation was carried out by five validators consisting of two biology education lecturers and three high school biology teachers. The validation results were then analyzed using the Lawshe formula. From the Lawshe formula, we use a validation sheet which is equipped with assessment criteria which can be seen in the validated results and discussion section. This research shows that the booklet media on biodiversity material is declared valid. Therefore, this booklet media on biodiversity material is suitable for use as a learning medium.